PENGUJIAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA SOLAR CELL KAPASITAS 50WP - Junial Heri (Universitas Pancasakti Tegal, 2012)
An electric voltage can be generated when a beam of sunlight which leads to a elektoda-electrode electrolytesolution. Less is more so who ever wrote Edmund Becquerel in 1839, research continues to exert a solid object inthe light of the sun, called selenium and until the cells potovoltaik (fhotovoltaic) with selenium and courprousmaterial, up to the experts succeeded in creating a photoelectric measuring devices. In 1954 the photovoltaic effectis developed again into electrical energy that is now called fotovoltaic cells or solar cells. In principle, solar cellsform conductive power semiconductor device which can directly convert solar energy into electrical energy in an efficient form of eco-friendly